Lexical Syntagms in Publicistic Prose - Muradyan, Gayane (Armenian Folia Anglistika, 2005)
The connection between lexical syntagms and functional-stylistic orientation in the Publicistic Prose is more evident due to adjectives ending in -able which, in fact, realize the category of the probability of the action. The wide use of lexical syntagms in the Publicistic Prose leads to stylistic marking and endows these units with a distinctive stylistic feature.